EFEITOS DA ASSOCIAÇÃO ENTRE GEL DE Cecropia glaziovii E LED 627nm NA CICATRIZAÇÃO DE LESÕES CUTÂNEAS POR SEGUNDA INTENÇÃO - Suckow, Patricia Pacheco Tyski (2021)
Healing is a complex and dynamic process that can be divided into phases with the aim of restoring damaged tissue and returning homeostasis. Pathologies that increase healing time can generate huge expenses with treatments and evidence the search for drugs and therapies capable of reacting with the injury, aiming to accelerate tissue repair. The use of photobiomodulation can be effective in tissue healing, with emphasis on the use of LED in tissue repair. Cecropia glaziovii SNETH, popularly known as “embaúba”, is a native species of Latin America, where it is used in different ways. In general, Cecropia is popularly used for the treatment of respiratory problems, such as cough, asthma and bronchitis, systemic arterial hypertension, diabetes and inflammatory processes, in addition to being used as a diuretic and cardiotonic. It has, in its chemical composition, bioactive compounds with anti-inflammatory and antioxidant activities. In this context, the present study aimed to verify the effects of 627nm LED and Cecropia glaziovii gel as isolated treatment and the association of the two treatments in the healing process in an experimental model. For this, a 3% sodium carboxymethylcellulose gel containing Cecropia glaziovii extract at 5% concentration was developed; the chosen concentration of the polymer was the ideal one to achieve the desired spreadability of the product as it had the best viscosity. Cecropia glaziovii gel was applied to the lesion before irradiation with 627nm LED. The in vivo evaluation was performed using a dorsal punch model, and the sample consisted of 96 Rattus Norvegicus rats, Wistar lineage, divided into 4 groups. Positive Control (CP), 627nm LED (LED), LED associated with Cecropia (LED+CEC) and Cecropia (CEC). All groups were analyzed at 3, 7, 14 and 21 days. The analyzes performed were: histological and histomorphometric, immunohistochemistry, flow cytometry, collagen by polarized light and macroscopic analysis. The collected data were analyzed statistically. It was observed that all treatment modalities presented good results, however, each one proved to be more adequate in different periods. Treatment with Cecropia glaziovii gel alone was superior in the first 7 days after the injury. The treatment using the association LED and Cecropia glaziovii gel showed greater potential between 7 and 14 days. And finally, the treatment with only LED was superior to the others in the last days of the process, between 14 and 21 days. It was concluded that the 3 types of treatment are promising for therapeutic applicability in healing processes, and given the results obtained, a more appropriate therapeutic protocol can be suggested as follows: daily application of Cecropia glaziovii gel in the first 7 days after the injury , daily application of the gel associated with 627nm LED irradiation between 7 and 14 days, and application of LED only between 14 and 21 days to complete the treatment.